Legislation Committee as Law Center in the National Law Development - Baidowi, Achmad (Sekolah Tinggi Agama Islam (STAI) Darul Ulum Banyuanyar Pamekasan, 2023)
The shift in the DPR legislative function after the amendment of the UUDNRI 1945, which was previously owned by the President then become the DPR function brought major changes. This change, plays an important role in the process of checks and balances and in enhancing the development of national law quality. However, this change is still not optimal. As can be seen from the fact that the legislative products produced by the DPR are not yet maximal, both quantitatively and qualitatively. Optimizing Baleg's position as a Law Center with the support of reliable supporting staff is one way to improve legislative performance. So far Baleg's role in carrying out its duties has not been optimal due to various interests which have hindered the drafting of the National Legislation Program and the deliberation of the Bill and the absence of a road map in monitoring and reviewing laws. Baleg's position as a Law Center must be strengthened to minimize the obstacles that arise so that the Prolegnas that have been set can be realized. Baleg needs to make arrangement so that the implementation of its duties can be optimal and ultimately able to improve the performance of the DPR in carrying out its powers as legislators. A road map in post legislative scrutiny needs to be made so it is clear that the implementation can be carried out in a directed and measurable manner.